2015
DOI: 10.1007/bf03404694
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic design of a light amphibious PrandtlPlane: wind tunnel tests and CFD validation

Abstract: Wind tunnel tests have been carried out on a ¼ scaled model of a two seats amphibian PrandtlPlane. In the present paper, CFD analyses, conducted with the Star-CCM+ software in order to replicate the experimental results, are presented. First, the full-scale free-air conditions have been simulated with a k-ε model and the results compared with those for the ¼ scaled model; the effects of the different Reynolds numbers are discussed. Then, by adding the elements connecting the model to the wind tunnel, i.e. the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Concerning the box-wing architecture characteristics at stall, as summarized in Cavallaro & Demasi (2016) for past NACA/NASA studies and experimentally shown in more recent works concerning the amphibious PrP "IDINTOS" (Frediani, et al, 2015) (Cipolla, et al, 2015), a proper box-wing system design makes the front wing more critical than the rear one. As confirmed also in the present paper, this behavior depends on the constraints of longitudinal trim and stability introduced in the box-wing design.…”
Section: State Of the Art Of Maximum Lift Coefficient Estimation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the box-wing architecture characteristics at stall, as summarized in Cavallaro & Demasi (2016) for past NACA/NASA studies and experimentally shown in more recent works concerning the amphibious PrP "IDINTOS" (Frediani, et al, 2015) (Cipolla, et al, 2015), a proper box-wing system design makes the front wing more critical than the rear one. As confirmed also in the present paper, this behavior depends on the constraints of longitudinal trim and stability introduced in the box-wing design.…”
Section: State Of the Art Of Maximum Lift Coefficient Estimation Methodsmentioning
confidence: 99%
“…The method has been validated considering the case of the box-wing 2-seats amphibian studied within the research project "IDINTOS" (Frediani, et al, 2015), for which a wind tunnel testing campaign has been carried out, as shown in Fig. 7 (Cipolla, et al, 2015). As Fig.…”
Section: Methods Validationmentioning
confidence: 99%
“…Whereas all the models provide a poor estimation of b -derivatives, the flat fuselage model is much more accurate in predictingaderivatives, and hence its choice represents the best compromise for the conceptual design phase. As detailed by Oliviero et al (2016), the research activities carried out during the project "IDINTOS" have provided both numerical and experimental results concerning the aerodynamics and flight mechanics of the PrP configuration in subsonic flight (Cipolla et al, 2016). Given the data shown in Figure 5 (Oliviero et al, 2016), at trim condition (a = 1°, b = 0°), the following accuracy factors can be calculated:…”
Section: Flight Mechanic Analysis Through Vortex-lattice Methods In Subsonic Rangementioning
confidence: 99%
“…In fact, although drag reduction is the main advantage of the PrP, other interesting benefits have been found for different aircraft categories. Previous studies have shown that the PrP has a smooth stall behavior and post-stall is characterized by only a partial reduction of maneuverability and controllability, 8 pitch control can be obtained by using counter-rotating elevators (on both front and rear wings) which can introduce a pitching moment without perturbation to lift, 9 the pitch damping is higher than in the case of a wing-tail configuration, with benefits in terms of comfort and safety. 10 In addition, as summarized in Cavallaro and Demasi 11 and Frediani et al., 12 the PrP configuration can be adopted for aircraft of very different dimensions, such as Light Sport Aircraft, ultra large airliners, freighter aircraft, 13 or “cryoplanes.” 14…”
Section: Introductionmentioning
confidence: 99%